Identification and counting of gastrointestinal parsasites in dorper sheep, in Atlapexco, Hidalgo, Mexico - Martínez-Martínez, Ricardo; Pérez-Bautista , José de Jesús; Hernández-Mogica, Martin; González Lemus, María Teresa; Austria Hernández, Isaí de Jesús; Mendoza Pedroza, Sergio Iban (Ecosistemas y Recursos Agropecuarios, 2022)
The objective was to identify and count the population of gastrointestinal nematodes (NGI) in a sheep production center in Atlapexco.A stool study was carried out using the McMaster technique, in 42 Dorper breed sheep, from September to November 2017 Descriptive statistics were performed on the evaluated variables (identification and count of NGI, age of the animals) with the STATISTICA® V 7.1. The genera of helminths found were Trichostrongylus spp., Trichurys spp. and Moniezia spp. It was found that sheep older than 12 months had a higher parasite load, which was 4742.8, while sheep less than 6 months old had 3800.0 NGI and those 6-11 months old was 2561.1 NGI. The identification and number of NGIs present in sheep will allow us to make preventive decisions to reduce parasite loads in Dorper sheep.